PROTEIN P53 SEBAGAI FAKTOR RISIKO TERJADINYA KETUBAN PECAH DINI - Donel Suhaimi (Universitas Padjadjaran, 2012)
Premature rupture of fetal membrane (PROM) is a complication in pregnancy that is an important problem in obstetrics. Manyteory have been explaining that cause of PROM, but the etiology is still unknown. Premature rupture of fetal membrane might be caused by apoptosis. The mechanism of PROM due to the apoptosis might cause the extracellular matrix degradation. The apoptosis is influenced by the signal from extracellular and intracellular protein. The intracellular factor is p53. This factors will cause a fetal membrane damage which induce increasing of caspase-3, so that the increasing of apoptosis in fetal membrane will cause the PROM. The present study is an observational analysis designed as a case-control study. The study was carried out in Dr. Hasan Sadikin Hospital and Central Laboratorium of Medical School of Padjadjaran University. The case group consist of 81 patients of PROM selected based on appropriate acceptance and rejection criteria taken by consecutive sampling. The control group consist of 81 patients with normal pregnancies at the age of ?37-<42 weeks gestation are taken by matching technique. Basic data included protein level of p53 by ELISA. Analysis of test results was conducted using bivariable analysis (Shapiro Wilk test, independent t test, Chi-square test, ANOVA test, Pearson analysis correlation and regression test) and multivariable (multiple logistic regression test). It was found that protein level of p53 was higher (>9,734 U/ml) than the normal pregnancy with p<0,0. The conclusion, there is a relationship protein level of p53 in the incidence of PROM. Protein levels of p53 was > 0,97 U/ml would increased in the incidence of PROM more than thirty times